2008
DOI: 10.4049/jimmunol.181.3.2134
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus Vector-Induced Innate Inflammatory Mediators, MAPK Signaling, As Well As Adaptive Immune Responses Are Dependent upon Both TLR2 and TLR9 In Vivo

Abstract: Adenovirus (Ad) vectors are promising candidates for both gene transfer and vaccine applications. In this study, we investigated the role of TLR2 in innate and adaptive immune responses to Ad and/or the transgene it expresses following systemic injection. We found that Ad directly activates ERK1/2 in vivo, but that initiation of ERK1/2 activation is primarily a MyD88/TLR2-independent, but Kupffer cell-dependent, event. The complexity of Ad-induced innate immune responses was confirmed when we also found that b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
199
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(205 citation statements)
references
References 34 publications
5
199
0
1
Order By: Relevance
“…As control Ad-EGFP was ineffective, the antitumor effect was not mediated by the induction of innate immunity upon vector injection. 35 These data further showed that RNAi of cell cycle-related genes (such as PLK-1) represents a viable option in the treatment of cancer. However, as our experiments have been performed in immunodeficient mice, we have not assessed the potential impact of the immune response against Ad vectors.…”
Section: Discussionmentioning
confidence: 90%
“…As control Ad-EGFP was ineffective, the antitumor effect was not mediated by the induction of innate immunity upon vector injection. 35 These data further showed that RNAi of cell cycle-related genes (such as PLK-1) represents a viable option in the treatment of cancer. However, as our experiments have been performed in immunodeficient mice, we have not assessed the potential impact of the immune response against Ad vectors.…”
Section: Discussionmentioning
confidence: 90%
“…7,20,22 It has also been shown that rAd injection results in evidence of Kupffer cell toxicity within 10 min of intravenous injection, followed by complete Kupffer cell depletion by 24 h after Ad injection. 27 For this reason, we evaluated rAd-induced Kupffer cell toxicity via F4/80 staining and fluorescence microscopy in Ad-injected C3-KO, FB-KO and C1q-KO mice at 24 h.p.i.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, we have recently revealed a similar result in Ad-injected Complement factors in innate and humoral immunity to Ad DM Appledorn et al TLR2-KO mice, and showed that IkBa degradation was completely dependent on MyD88 functionality. 7 The possibility of a direct or indirect interaction between complement and TLR-mediated signaling pathways is intriguing and relatively understudied. 33,34 Interestingly, we did not detect a role for C3 in rAd-induced ERK1/2 activation.…”
Section: Complement Factors In Innate and Humoral Immunity To Ad Dm Amentioning
confidence: 99%
See 1 more Smart Citation
“…Insufficient co-stimulation may induce tolerance. 6 Adenoviral vectors engage pattern recognition receptors such as Toll-like receptor (TLR)2 and TLR9 [7][8][9] known to initiate pro-inflammatory responses and to induce expression of co-stimulatory molecules.…”
mentioning
confidence: 99%